Book review: Robert D. Hisrich and Veland Ramadani (Eds), Entrepreneurial Marketing: A Practical Managerial Approach. (September 2019) - Kumar, Pranav
Robert D. Hisrich and Veland Ramadani (Eds.), Entrepreneurial Marketing: A Practical Managerial Approach, Cheltenham, UK: Edward Elgar Publishing, 2018, 202 pp.